Konektifitas Al-Quran: Studi Munasabah Antar Ayat Dan Ayat Sesudahnya Dalam Qs. Al-Isra’ Pada Tafsir Al-Misbah - Ahmad Ghozali; Indra Saputra (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2021)
This paper aims to determine the attitude of the commentators on munasabah in the interpretation of the Qur'an and the interpretation of M. Quraish Shihab towards the munasabah verse with the verse after it in QS. Al-Isra' on Tafsir Al-Misbah. This research is a qualitative research. Primary data sources in the form of Tafsir Al-Misbah by M. Quraish Shihab Volume 7, and secondary sources in the form of the book